Haemolytic Diseases of Newborn (HDN)- A Case report - Khatun, Ayesha; Biswas, Jolly; Habibullah, MM; Rahman, Atiar; Bhuiyan, Zillur Rahman; Biswas, Danis Arefin (Bangladesh Medical Journal, 2019)
Allo-antibody mediated Haemolytic diseases of newborn in the common term of blood group fetomaternal incompability. Most of the HDN are due to Anti-D allo antibody of a D-Negative mother where the child is D positive1. In this case study we describe an unusual HDN in a D+ve mother where the child is also D positive. Fetomaternal incompability is a clinical syndromes in the fetus Caused by the placental transfer of a maternal allo-antibody. Blood group incompability is the major cause of incompability. Among blood groups ABO, Rhesus, Kell, Kidd, Duffy are mostly involve in HDN. About 2/3rd of all pregnancy are ABO incompatible, but it is of very mild type and usually not identified. But rhesus & others blood groups involve rest 1/3rd incompatibility, which are severe form of HDN. Bangladesh Med J. 2017 May; 46 (2): 59-60